Comparative and international education issues for teachers - Bickmore, Kathy; Hayhoe, Ruth; Manion, Caroline; Mundy, Karen E.; Read, Robyn (Canadian Scholars, 2017)
This edited collection explores the field of comparative and international education as it relates to the work of teachers. The book introduces Education students to research in comparative and international education, provides an overview of international issues in education, and explores education in diverse settings. The chapters draws on comparative research from around the globe and explore themes such as the history and philosophy of comparative education, the right to education, alternative pedagogies, gender, Indigenous knowledge, peace building, international assessments, and global citizenship. This expanded second edition has been thoroughly updated and contains two new chapters on human rights education and the internationalization of schooling. It also includes a stronger focus on teachers and their involvement in international education and on issues of diversity and social justice education. New scholars from around the world have contributed to this edition in order to give the scholarship a more international scope."--